On the Mutual Influence of Voltage Control Modes and the Compensation of Reactive Power in the Electrical Networks of Industrial Enterprises - V. P. Schasny; A. I. Zhukouski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The efficiency of an enterprise’s power supply system depends on the quality of electricity and the losses of the latter in electrical networks; both being largely determined by the modes of voltage control and reactive power compensation. In practice, the problems of voltage control and reactive power compensation in power supply systems of industrial enterprises, including electric networks with a voltage of up to 1 kV, as well as 6, 10 kV and higher, are often solved separately. It triggers an irrational use of existing voltage control devices, underutilization of the installed capacity of compensating devices, and affects the voltage control in the electrical networks of the power supply organization. Since voltage management and compensation modes of reactive power are inseparable, they can be correctly determined only with the use of an integrated approach based on technical and economic criteria and taking into account technical requirements and local conditions. This article analyzes the mutual influence of voltage control and reactive power compensation modes in the electrical networks of industrial enterprises from the point of view of ensuring the quality of electricity and minimizing load power losses. The method and results of calculations (on the example of a specific industrial facility) for determining voltage deviations and losses in the electrical network as well as for selecting parameters for voltage control and reactive power compensation are presented. Due to the close relationship of these modes that affect all voltage levels, the effectiveness of measures cannot be ensured without the use of multifunctional devices for controlling the equipment of transformer substations.